Mission: green. - Brock, Ed (American City & County, 2008)
This article explores the move of many cities and counties in the U.S. to adopt environmental conservation and sustainability programs. According to the author, many cities and counties are enlisting consultants to plan waste reduction programs, preserve water resources and help measure carbon emissions. He cites the launch of a recycling program and incentives by the city government of Austin, Texas, to encourage residents to produce less waste